Analisis Tindak Tutur Ilokusi Pada Tajuk Rencana Surat Kabar Solopos Dan Implementasinya Terhadap Pembelajaran Bahasa Indonesia Di Smp - Dewi, Iin Rosiana; , Dr. Yakub Nasuha,M.Hum (2017)
The research of this study has three purpose. 1) The tye of the speech actof the editorial illocution on Solopos spapers January 2017. 2) The function of the speech act of the editorial illocution on Solopos newspapers January 2017. 3) The implementation of the speech act of the editorial illocution on Solopos newspaper January 2017 toward of the Indonesian language learning at SMP. The type of this research was descriptive qualitative research. The data of this study was speech act of the illocution. The technique of collecting data used scrutinized note method. The technique of analysis model. The type of this analysis has three components analysis: data reduction, data resentation, and data conclusion or verifications. There are three aspect that indication in this study. 1) All of the result of this study has speakers and speech partners. 2) The result of the study were: a) Assertive speech act was guessing and fying. b) Commissive speech act proposing. c) Directive speech act was instructing and advices. d)Decleration speech act was punishment. e) Competitive speech act was required. f) Conventions speech act was offered, invited and reccomended. g) Collaborations speech act was reported. h) Conflictful speech acts include threatening, coercing, rebuking, and respect. 3) This research will be implemented in learning Indonesian language at Junior High School (SMP). The relevance of the material taught is the material about the interview.